Ratio of carcinoembryonic antigen in pleural fluid and serum for the diagnosis of malignant pleural effusion. (May 2019) - Hackner, Klaus; Errhalt, Peter; Handzhiev, Sabin
Background: Tumour markers in pleural fluid and their diagnostic value are subject to debate. Although there are several studies on this topic, standardized cut-off values do not exist. In this study we investigated the potential of a ratio of carcinoembryonic antigen (CEA) in pleural fluid and serum, serving as an individual marker for pleural cancer manifestation. Methods: A total of 201 consecutive patients with unclear pleural effusion were included in the study; 98 were diagnosed with malignant pleural effusion and 103 had an effusion due to other, benign reasons. CEA levels in pleural fluid and serum were measured. Results: By using receiver operating characteristics analysis, at the cut-off of 1.0, the CEA ratio showed a specificity of 92% and sensitivity of 85%, with a positive predictive value of 91% and a negative predictive value of 87%. These results are higher than in previous investigations on different pleural tumour markers and their combination. Conclusions: The CEA ratio is a useful tool in predicting pleural carcinosis. Elevated results in cytology-negative patients should lead to further investigations, such as repeated cytological examination or thoracoscopy.